Does Thrifting Undermine Local Brands? A Descriptive Study on Fashion Consumption Trends and Purchase Intentions - Hardya Alisya; Wenny Pebrianti; Heriyadi (Al-Qalam Institue, 2026)
This study aimed to analyze the thrifting phenomenon by examining how fashion trends, price, brand image, and consumer ethnocentrism shape purchase intention toward Indonesian local fashion products. This study employed a quantitative research design with a descriptive approach. Data were collected through questionnaires distributed to consumers who had experience with thrift fashion products. Respondents were selected using purposive sampling based on predetermined criteria. The collected data were analyzed descriptively by calculating the mean score of each indicator and interpreting the results based on predefined scale intervals. The findings reveal that purchase intention toward local Indonesian fashion products is formed through a multidimensional evaluation process involving economic, symbolic, and emotional considerations. Price was identified as an important factor influencing thrift product attractiveness, while brand image showed a relatively moderate role in consumer decision-making. Meanwhile, consumer ethnocentrism demonstrated positive support for local fashion products without eliminating interest in thrift alternatives. This study implies that local fashion businesses should strengthen product quality, brand value, and consumer attachment to compete within the growing thrift fashion market. The findings contribute to a broader understanding of consumer behavior by highlighting the coexistence between thrift culture and local fashion preference.